Educación para la salud laboral: Perspectivas teóricas desde la intervención. - Rivera-Porras, Diego; Bonilla-Cruz, Nidia-Johanna; Carrillo-Sierra, Sandra-Milena; Forgiony-Santos, Jesús; Silva-Monsalve, Gloria (Archivos Venezolanos de Farmacología y Terapéutica, 2019)
The purpose of this article is to review the literature on occupational health, its implications on employees, the risk factors to which they are exposed and the various diseases or syndromes that deteriorate the health of members of the organization. To fulfill this objective, a bibliographic design of documentary type was approached; whose source of information was secondary data. It is concluded that, occupational health is related to the way employees assume it and not only depends on the actions carried out by the company, it is also built in a healthy working environment and adequate conditions, however, occupational health can be impaired by various factors in the work environment, stressing that stress is the main cause of health deterioration, causing cardiovascular, metabolic diseases and Burnout syndrome.